1998
DOI: 10.1136/vr.142.24.656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovariohysterectomy in bitches with mammary neoplasms

Abstract: Ninety bitches with mammary tumours were studied for two years after the surgical removal of the primary tumour(s). Twenty-nine of the bitches had been spayed before the development of the mammary tumour, 22 were spayed when the tumours were removed and 39 were left entire. Fifty-eight of the bitches (64 per cent) had benign tumours and, of these, 15 (26 per cent) developed a new mammary tumour within two years, irrespective of whether the bitch was spayed. The other 32 bitches had malignant tumours which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
20

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 13 publications
3
36
0
20
Order By: Relevance
“…By these results we can conclude that spaying is a more preservative factor than giving birth for the formation of malignant mammary tumours. Parallel to our findings previous researchers [22,25,26] verify that in bitches ovariectomy offered a protective effect against the development of this condition and this effect is most pronounced if this operation is performed early in life, before 2.5 years of age.…”
Section: Discussionsupporting
confidence: 78%
“…By these results we can conclude that spaying is a more preservative factor than giving birth for the formation of malignant mammary tumours. Parallel to our findings previous researchers [22,25,26] verify that in bitches ovariectomy offered a protective effect against the development of this condition and this effect is most pronounced if this operation is performed early in life, before 2.5 years of age.…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, other studies have reported that ovariectomy at the time of mastectomy has no effect on the prognosis of CMT (Yamagami et al, 1996b;Morris et al, 1998). A recent study has demonstrated that ovariohysterectomy performed at the time of tumor excision reduces the risk of new tumors by about 50% among bitches with BMT (Kristiansen et al, 2013).…”
Section: Conventional Therapies and New Treatment Strategiesmentioning
confidence: 91%
“…Dados semelhantes ao deste estudo, sobre a maior frequência de neoplasias mamárias malignas em relação ao total, também foram observados por outros autores (Green et al, 2009, Oliveira Filho et al, 2010. Contudo é presuntivo que estudos baseados em biopsias remetidas a laboratórios tenham prevalência maior de casos malignos, devido a suspeita de comportamento biológico (Morris et al, 1998 Archives of Veterinary Science, v. 18, (supl.2) RESUMO 201, 2013 551 Archives of Veterinary Science, v. 18, (supl.2) RESUMO 201, 2013 552 foram observadas nos ductos coletores e elas sugerem dano ou doença renal de causa aguda (ASLANI et al, 2007). O tratamento da intoxicação por N. oleander consiste em dar suporte com fluidoterapia via oral ou intravenosa para diminuir os efeitos cardiovasculares (HUGHES et al, 2002).…”
Section: Resultsunclassified
“…Dados semelhantes ao deste estudo, sobre a maior frequência de neoplasias mamárias malignas em relação ao total, também foram observados por outros autores (Green et al, 2009, Oliveira Filho et al, 2010. Contudo é presuntivo que estudos baseados em biopsias remetidas a laboratórios tenham prevalência maior de casos malignos, devido a suspeita de comportamento biológico (Morris et al, 1998). Entre os tumores benignos, houve maior prevalência dos adenomas, o que se assemelha ao verificado por Green et al (2009 Cassali (2006), verificou-se que a idade média no momento diagnóstico está entre nove e 11 anos para cadelas, indicando que animais jovens são dificilmente acometidos.…”
Section: Methodsunclassified